Aggregate employment, job polarization and inequalities: A transatlantic perspective - Julien Albertini; Jean Olivier Hairault (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
This paper develops a multi-sectorial search and matching model with endogenous occupational choice in a context of structural change. Our objective is to shed light on the way labor market institutions affect aggregate employment, job polarization and inequalities observed in the US and in European countries. We consider the cases of the US, France and Germany that are representative of alternative institutional settings, having the potential to induce divergent time-paths in the evolution of labor market outcomes during the process of technological transition. In the US and in Germany, we find employment gains from technological change and job polarization, whereas, in France, the technological change reduces aggregate employment in a context of job polarization. In the US, an half of these employment gains are due to the technological change, and the other half to the changes in the LMI, the contribution of the rise in share of skilled worker being negligible. In France, the change in LMI affects new job opportunities in manual jobs: the reallocation of routine workers towards manual jobs is obstructed for want of job creations of manual services. Hence, without technological change, the fall in French employment would have been cut by 70%. The model also predicts that, without the increase in skilled labor supply, the fall in French employment would have doubled. The improvement in educational attainment dampened the unfavorable consequences of technological change. we show that Germany transforms this structural change in employment gains, only after the labor reforms implemented after the middle of the 90s.
Keywords: E24; J62; J64; O33; 330; search and matching; job polarization; reallocation; labor market institutions